On “commons” and New Institutional Economics: a “precursor” revisited - Jens Warming (1873-1939) - Pacheco Coelho, Manuel (Iberian Journal of the History of Economic Thought, 2016)
In his seminal paper, Gordon (1954) argued that, in a situation of open access and competition, the market would not lead to the most efficient solution in resource use. Almost four decades earlier, in 1911, a Danish economist, Jens Warming, put this issue and made a very similar analysis for the fisheries sector. The purpose of this research is to make a reflection on that paper and highlight the proposed explanation for the common property problem. This paper studies the legacy of this interesting fisheries economist to the history of economic thought and put in evidence its role as a “precursor” in important topics of investigation of the New Institutional Economics. This research also ask what went wrong and why did the important achievements of Warming’s research had not the justified academic applause and practical impact.